2021
DOI: 10.1088/1742-6596/2112/1/012024
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of High Temperature Weather on Human Body Temperature Measurement by Infrared Thermal Imaging Thermometer

Abstract: Infrared thermography thermometer is a non-contact temperature measuring equipment, which is widely used in the stage of large-scale epidemic of the covid-19 pandemic. It is used for rapid screening of human body temperature in crowded places at the entrance and exit of airports, docks, shopping malls, stations and schools. But when the outdoor temperature approaches or exceeds the body temperature in summer, can this method of measuring body surface temperature by infrared thermal imager be used as a standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Weather-related factors such as temperature, relative humidity, and wind velocity have also been found to be significantly correlated with patient body temperature, with effects varying in magnitude depending on the distances from outside to the measurement site (Spindel et al, 2021). For example, high environmental temperatures (above 99.5 °F) readily affect shell (skin) temperature and infrared thermometry measurements (Mei et al, 2021). Another study found that skin temperature was significantly affected by ambient temperature in both hot and cold conditions (Strigo et al, 2000).…”
Section: Work Citedmentioning
confidence: 99%
“…Weather-related factors such as temperature, relative humidity, and wind velocity have also been found to be significantly correlated with patient body temperature, with effects varying in magnitude depending on the distances from outside to the measurement site (Spindel et al, 2021). For example, high environmental temperatures (above 99.5 °F) readily affect shell (skin) temperature and infrared thermometry measurements (Mei et al, 2021). Another study found that skin temperature was significantly affected by ambient temperature in both hot and cold conditions (Strigo et al, 2000).…”
Section: Work Citedmentioning
confidence: 99%
“…The experiments in simulated/actual environmental conditions in [ 9 ] proved that there must be an acclimatization period ranging from 2 to 9 min depending on the outdoor temperature before temperature screening. The use of relative temperature difference for screening patients with fever is recommended in [ 10 ] in the case of ambient temperatures higher than 37.5 °C.…”
Section: Introductionmentioning
confidence: 99%